2016
DOI: 10.1371/journal.pone.0167633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Biodentine® - A Dentine Substitute - On Collagen Type I Synthesis in Pulp Fibroblasts In Vitro

Abstract: Preserving a patient’s own teeth—even in a difficult situation—is nowadays preferable to surgical intervention and therefore promotes development of suitable dental repair materials. Biodentine®, a mineral trioxide aggregate substitute, has been used to replace dentine in a bioactive and biocompatible manner in both the dental crown and the root. The aim of our study was to evaluate the influence of Biodentine® on pulp fibroblasts in vitro. For this study, one to five Biodentine® discs with a diameter of 5.1mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
0
10
0
5
Order By: Relevance
“…In part, this is explained because all materials used in the study, both glass ionomers and antimicrobials, have a reported degree of toxicity [48,49]. Different in vitro studies assessed the cytotoxicity of GICs and RMGICs on cultured cells Journal of Nanomaterials [42][43][44][45][46][47][48][49][50][51][52]. The studies have supported the concept that leachable components of the dental materials are responsible for the cytotoxicity in cell culture.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In part, this is explained because all materials used in the study, both glass ionomers and antimicrobials, have a reported degree of toxicity [48,49]. Different in vitro studies assessed the cytotoxicity of GICs and RMGICs on cultured cells Journal of Nanomaterials [42][43][44][45][46][47][48][49][50][51][52]. The studies have supported the concept that leachable components of the dental materials are responsible for the cytotoxicity in cell culture.…”
Section: Discussionmentioning
confidence: 95%
“…The in vitro studies can be conducted under controlled conditions and provide a significant amount of information [38]. Different cell lines are used to probe the biocompatibility of dental materials like pulp cells extracted from the maxillary incisors of Sprague Dawley rats, multipotent stromal cells, human foreskin fibroblast, human lung fibroblast, primary human osteoblast, L929 mouse fibroblast, SV40 large T-antigen-transfected bovine dental pulpderived cells, MDPC-23 odontoblast-like cell line, primary pulp fibroblast, and human alveolar osteoblast, for example [39][40][41][42][43][44][45][46]. In this study, the MA-104 epithelial cell line was used because the glass ionomer cements are in direct contact with the epithelial tissue of the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated by Loison-Robert and colleagues [ 28 ], Biodentine promotes mineralization when in contact with dental pulp stem cells (DPSCs); however, it does not affect DPSC proliferation. Interestingly, the only biological factor that Biodentine has shown to increase is TGF-β1 [ 29 ]; however, Neves and Sharpe [ 30 ••] showed that TGF-β and BMP are not pivotal for reactionary dentine formation but for tubular organization of reactionary dentine secretion. Reactionary dentine secretion is affected, however, by changes in the Wnt pathways.…”
Section: Healing and Engineering Different Dental Tissuesmentioning
confidence: 99%
“…Investigaciones odontológicas recientes dentro de un enfoque integral consideran, cada vez más, los dientes y la salud oral como parte de la salud del organismo 1 . Ya no sólo es el dentista el que intenta educar, sino que la población, que engloba tanto a los pacientes como a profesionales de otras áreas de la salud, está mostrando un interés cada vez mayor por la conservación dental.…”
Section: Introductionunclassified
“…del fraguado y un polímero hidrosoluble que actúa como agente reductor de agua 1,2,[5][6][7][8][9][10][11] .…”
unclassified